A Characterization and Pedagogical Analysis of Youth Entrepreneurship. (3rd April 2023) - Hadley, Gregory R. L.
This paper proposes a characterization of the youth entrepreneur and, subsequently, explores pedagogies that can assist in the development of entrepreneurial knowledge, skills and attitudes (KSAs) among youth in a secondary school context. Data was collected via a mixed methods approach. A small cross-section of high school students from the Canadian province Nova Scotia participated in a semi structured interview on entrepreneurship and pedagogy, while a larger cross-section completed a survey that assessed perceived degree of entrepreneurialism. The study concluded that young people possess, to varying degrees, a variety of entrepreneurial knowledge, skills and attitudes. Furthermore, it was found that those KSAs are largely gathered, refined and mobilized in extra-curricular contexts, leaving secondary schools to consider how to better support the entrepreneurialism of their students. The various implications of these findings, as they relate to pedagogy, practice, and educational policy are explored in detail.